A review of the land birds of the West Sumatran Islands - Derek A Holmes (Indonesian Ornithologists’ Union, 1994)
A perusal of the distribution list in the BOU Sumatran Checklist (Mark & Voous 1988) indicates a need for a systematic review of the birds of the West Sumatran islands. The objective of this paper is to summarize every species of land bird that has been recorded on each of the main islands, and to highlight those for which substantiating field records have been collected since 1970. At the same time, the opportunity is taken to comet any omissions and errors in the Checklist, and to add recent new island records.